Population differentiation and genetic diversity of endangered Brachymystax tsinlingensis Li between Yangtze River and Yellow River in China based on mtDNA. (4th July 2019) - Shao, Jian; Xiong, Dongmei; Chu, Zhipeng; Wu, Jinming; Du, Hao; Wang, Feng; Wen, Sien; Wei, Qiwei
Abstract: Brachymystax tsinlingensis Li, distributed scatteredly in Qinling Mountains of China, is an ideal material for studies of conservation and phylogeography. In the present study, the genetic variations and phylogeographical patterns of B. tsinlingensis collecting from the Yangtze River ( n = 30) and the Yellow River ( n = 70) were compared based on 1082-1163 bp control region with partial tRNA and 912 bp cyt b partial sequence of mtDNA. Analysis of variance indicated that a high proportion of the total genetic variance (96.03%) was distributed among populations, supporting strong geographic structuring of mtDNA polymorphism. Ten haplotypes were assigned to two clades that were related to geographic regions. No haplotype shared between geographic populations from the Yangtze River and the Yellow River, and two clades related to geographic regions can be clearly found from phylogenetic analysis by Bayesian approach, one from individuals in the Yangtze River and the other from individuals in the Yellow River, which probably indicated artificial carrying not happened historically. The mitochondrial results revealed an obvious differentiation of genetic structure of B. tsinlingensis between populations of Yellow River and Yangtze River, and the estimated diverge time around 0.20 MY. It was suggested that each of the two evolutionarily distinct groups of B. tsinlingensis should be protected and crossing individuals between two river systems should be avoided for conservation purpose.